Essays on the impact of government assistance, capital regulation, and COVID-19 on banks - Palas, Md Jahir Uddin (The University of Edinburgh, 2023)
This thesis includes three empirical studies that investigate the causal impact of government assistance, capital regulation, and COVID-19 on banks. While the first two essays are based on the US banking sector, the third essay analyzes a multinational sample. The studies are structured in a self-contained manner that enables independent reading. The first study examines the impact of government support on recipient banks’ funding costs. The US government’s Capital Purchase Program (CPP) is utilized as a case study of government assistance. The results suggest that government aid has a significant relationship with the recipient banks’ lower funding costs. Augmented public confidence in recipient banks could be a plausible explanation for the government assistance-funding cost relationship. I contribute to the pertinent literature by providing possibly the earliest empirical evidence on funding cost that is fundamental to banks’ core business yet largely ignored in government assistance research. The second study revisits banks’ capital-risk nexus with a novel regulatory setting. While stringent capital requirements can lead to less risk-taking by ensuring more ownership, banks can also increase risk-taking as a response to the increased cost of capital. However, relevant literature lacks evidence when such requirements are voluntary, aimed at small banks, and disregard the risk-based approach. Likewise, the role of banks’ risk appetite in this interconnection is not fully explored. I exploit the Community Bank Leverage Ratio (CBLR) Framework in the US to fill the aforementioned literature gaps. I find that CBLR has a significant relationship with aggressive banks’ increased risk-taking. Tougher capital rules, when voluntary and non-risk-based, offer incentives that motivate aggressive banks’ adoption and result in more risk-taking. Due to heightened risk-taking, I raise concerns about the appropriateness of capital rules exclusively based on a single leverage ratio instead of a risk-based approach. The third study investigates the impact of the COVID-19 pandemic on banks’ cost efficiency. The pandemic brought economy-wide uncertainty, unforeseen challenges, and a radical shift in banking operations that can have efficiency implications. Empirical evidence suggests that the pandemic contributed to increased efficiency in banks. Banks’ prudential approach, gains from digital banking and remote work, and reduced staffing costs can be some of the possible explanations for the finding. I contribute to the comparatively less explored bank efficiency domain in COVID-19 literature by examining the cost efficiency impact through stochastic frontier analysis and the moderating effects of country-level factors in such impact. Additionally, I question the validity of the exogeneity assumption mostly found in related research and argue that while the emergence of COVID-19 may be exogenous, its spread is perhaps not, requiring endogeneity treatments in multiperiod analyses. My research has important implications for regulators, bank managers, and financial market participants. First, findings from the three essays will enable regulators to design better intervention programs, capital regulations, and disaster preparedness policies. The outcomes tested in this thesis, namely funding cost, risk-taking, and efficiency, are highly relevant to bank stability discussions that are of greater significance to regulators. Second, bank managers will benefit from an improved understanding of the aftermaths of receiving government assistance, opting for stringent capital, and operational challenges of COVID-19. All of which will contribute towards robust bank management strategies. Finally, the conclusions will facilitate market participants' analysis of bank behavior and estimation of potential outcomes under different regulatory and economic settings.
Keywords: government assistance; capital regulation; COVID-19; US banking sector; Capital Purchase Program; capital-risk nexus; Community Bank Leverage Ratio; banks’ cost efficiency; cost efficiency; bank behavior